Determinants of the flow of bilateral adaptation-related climate change financing to sub-Saharan African countries: The extent to which environmental, economic, historical and political factors play a role - Jamie Robertsen; Nathalie Francken; Nadia Molenaers (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2015)
The apparent mismatch between countries receiving Adaptation-related Climate Change Financing (ACCF) and those most vulnerable to climate change is a concern which is the motivation for this research. This paper examines the determining factors of receiving ACCF for sub-Saharan African countries and finds that the recipient policy and an existing aid relationship are significant determinants of funding. ACCF therefore appears to be contingent on democratic characteristics of the recipient and prevailing a donor-recipient relationship, with vulnerability not being a factor. Our research draws a parallel between ACCF and traditional, bilateral aid allocation, and stresses the importance of accurate climate finance allocation practices.
Keywords: 330; Internationale Klimapolitik; Finanzierung; Entwicklungshilfekonditionen; Vulnerabilitätsanalyse; Subsahara-Afrika